Field Electron Emission from Pyrograf Ш PR-1 Carbon Nanotube Fibers Embedded in Glass - M. S. Mousa; M.-A. H. Al-Akhras; S. I. Daradkeh (Jordan Journal of Physics, 2025)
This study investigates the field electron emission properties of Pyrograf-Ш carbon nanotube fibers (CNTFs). Field emitters were manufactured by employing a drawing technique using a glass puller. A field electron microscope with a tip (cathode) to screen (anode) separation of approximately 10 mm was used to characterize the emitters. The current-voltage (I-V) characteristics of the CNTFs showed a shallow increase in the emitted current with increasing applied voltage, until a threshold voltage (VTH) is reached, after which a “switch-on” phenomenon occurs. The I-V characteristics are then linear. Fowler-Nordheim plots and field electron emission patterns are also discussed and it is shown that it is possible to get a single bright emission spot. Keywords: Field electron emission, Carbon nanotube fibers (CNTFs).